Nationwide surveillance of bacterial respiratory pathogens conducted by the surveillance committee of Japanese Society of Chemotherapy, the Japanese Association for Infectious Diseases, and the Japanese Society for Clinical Microbiology in 2012: General view of the pathogens' antibacterial susceptibility. Issue 9 (September 2017) - Yanagihara, Katsunori; Watanabe, Akira; Aoki, Nobuki; Matsumoto, Tetsuya; Yoshida, Masaki; Sato, Junko; Wakamura, Tomotaro; Sunakawa, Keisuke; Kadota, Junichi; Kiyota, Hiroshi; Iwata, Satoshi; Kaku, Mitsuo; et al.
Abstract: The nationwide surveillance on antimicrobial susceptibility of bacterial respiratory pathogens from the patients in Japan was conducted by Japanese Society of Chemotherapy, Japanese association for infectious diseases and Japanese society for Clinical Microbiology in 2012. The isolates were collected from clinical specimens obtained from well-diagnosed adult patients with respiratory tract infections during the period between January and December in 2012 by three societies. Antimicrobial susceptibility testing was conducted at the central reference laboratory according to the method recommended by Clinical Laboratory Standard Institutes. Susceptibility testing was evaluated in 1236 strains (232 Staphylococcus aureus, 225 Streptococcus pneumoniae, 16 Streptococcus pyogenes, 231 Haemophilus influenzae, 147 Moraxella catarrhalis, 167 Klebsiella pneumoniae and 218 Pseudomonas aeruginosa ). Ratio of methicillin-resistant S. aureus was 51.3%, and those of penicillin-intermediate S. pneumoniae was 0.4%. Among H. influenzae, 5.6% of them were found to be β-lactamase-producing ampicillin-resistant strains, and 37.2% to be β-lactamase-non-producing ampicillin-resistant strains. Extended spectrum β-lactamase-producing K. pneumoniae and multi-drug resistant P. aeruginosa with metallo β-lactamase were 4.2% and 3.2%, respectively. Continuous national surveillance is important to determine the actual situation of the resistance shown by bacterial respiratory pathogens to antimicrobial agents.